The coronavirus pandemic and food security: Evidence from Mali. (May 2021) - Adjognon, Guigonan Serge; Bloem, Jeffrey R.; Sanoh, Aly
Highlights: We estimate changes in experienced food insecurity associated with the coronavirus pandemic. We combine pre-pandemic survey data with follow-up phone survey data from Mali. Prior to the pandemic rural households were more likely to experience food insecurity. Three months after the onset of the pandemic, the rural–urban gap in food insecurity vanished. Understanding heterogeneity in changes in food insecurity is critical to post-pandemic policy. Abstract: This paper documents some of the first estimates of changes in experienced food insecurity associated with the coronavirus pandemic in a low-income country. It combines nationally representative pre-pandemic household survey data with follow-up phone survey data from Mali and examines sub-national variation in the intensity of pandemic-related disruptions between urban and rural areas. Although rural households are more likely to experience food insecurity prior to the pandemic, we find that food insecurity increased more in urban areas than in rural areas. Just three months after the onset of the pandemic, the rural–urban gap in experienced food insecurity completely vanished. These findings highlight that understanding effect heterogeneity is critically important to effectively designing and targeting post-pandemic humanitarian assistance.